2014
DOI: 10.1128/mcb.00799-14
|View full text |Cite
|
Sign up to set email alerts
|

Release Factor eRF3 Mediates Premature Translation Termination on Polylysine-Stalled Ribosomes in Saccharomyces cerevisiae

Abstract: bRibosome stalling is an important incident enabling the cellular quality control machinery to detect aberrant mRNA. Saccharomyces cerevisiae Hbs1-Dom34 and Ski7 are homologs of the canonical release factor eRF3-eRF1, which recognize stalled ribosomes, promote ribosome release, and induce the decay of aberrant mRNA. Polyadenylated nonstop mRNA encodes aberrant proteins containing C-terminal polylysine segments which cause ribosome stalling due to electrostatic interaction with the ribosomal exit tunnel. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 91 publications
3
63
0
1
Order By: Relevance
“…Polybasic proteins cause similar effects, as demonstrated by our analysis and by different groups. [4][5][6][25][26][27] Our analysis, together with other recent studies exploring the effect of CHX on ribosome profiling, 23,28 showed, that the RP methodology can be more faithfully used to explore ribosomal translation if performed in the absence of translational inhibitors such as cycloheximide and anisomycin. We demonstrated that drug-free RP datasets tend to agree with the experimental evidence obtained by other methods analyzing the role of positively charged amino acids in reducing protein translation.…”
Section: Resultsmentioning
confidence: 95%
“…Polybasic proteins cause similar effects, as demonstrated by our analysis and by different groups. [4][5][6][25][26][27] Our analysis, together with other recent studies exploring the effect of CHX on ribosome profiling, 23,28 showed, that the RP methodology can be more faithfully used to explore ribosomal translation if performed in the absence of translational inhibitors such as cycloheximide and anisomycin. We demonstrated that drug-free RP datasets tend to agree with the experimental evidence obtained by other methods analyzing the role of positively charged amino acids in reducing protein translation.…”
Section: Resultsmentioning
confidence: 95%
“…Intriguingly, there is prior evidence that Sup45–Sup35 may be capable of binding to stalled ribosomal complexes that contain a sense codon in the A site (63,64,28). Another interesting question concerns the activity of Ltn1 on 60S·NC substrates in the absence of tRNA or Rqc2.…”
Section: Discussionmentioning
confidence: 99%
“…Although no stop codon is involved, eukaryotic translation release (termination) factors 1 and 3 (eRF1/eRF3) are proposed to release the nascent protein from the ribosome, thereby forming the C-terminus of 2A ( Figure 2). In support of this model, eRF3 was recently shown to mediate termination of translation of yeast ribosomes stalled on polylysine tracts (17), although other recent analyses using re-constituted translation systems did not support the involvement of eRFs 1 and 3 (18). Our model of this translational recoding event predicts that three alternative outcomes arise; having synthesized sequences upstream of 2A, ribosomes either (i) resume translation of the downstream sequences, (ii) translation is and 'cleaved' [GFP-2A] plus GUS translation products.…”
mentioning
confidence: 89%